2018
DOI: 10.1007/s12035-018-1195-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-Driven Neuroinflammation Compromises BBB Leading to Memory Loss in Both Diabetes Mellitus (DM) Type 1 and Type 2 Mouse Models

Abstract: End organ injury in diabetes mellitus (DM) is driven by microvascular compromise (including diabetic retinopathy and nephropathy). Cognitive impairment is a well-known complication of DM types 1 and 2; however, its mechanism(s) is(are) not known. We hypothesized that blood-brain barrier (BBB) compromise plays a key role in cognitive decline in DM. Using a DM type 1 model (streptozotocin injected C57BL/6 mice) and type 2 model (leptin knockout obese db/db mice), we showed enhanced BBB permeability and memory lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(148 citation statements)
references
References 80 publications
(113 reference statements)
3
142
0
3
Order By: Relevance
“…Further, these aberrant mitochondria may result in damage not only to the inner membranes but also the outer mitochondrial membranes that may allow for herniation and loss of the mitochondrial matrix proteins and sometimes result in mitochondria swelling ( Figure 15) [23]. Recently, there has been an interest in hyperglycemia-driven neuroinflammation, which may compromise the integrity of BBB with increased permeability that leads to memory loss and impaired cognition [18]. This, along with the increasing interest in the vascular contributions to cognitive impairment and dementia, wherein scientific experts convened to discuss the research gaps in our understanding of how vascular factors contribute to Alzheimer's disease and related dementia has been discussed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, these aberrant mitochondria may result in damage not only to the inner membranes but also the outer mitochondrial membranes that may allow for herniation and loss of the mitochondrial matrix proteins and sometimes result in mitochondria swelling ( Figure 15) [23]. Recently, there has been an interest in hyperglycemia-driven neuroinflammation, which may compromise the integrity of BBB with increased permeability that leads to memory loss and impaired cognition [18]. This, along with the increasing interest in the vascular contributions to cognitive impairment and dementia, wherein scientific experts convened to discuss the research gaps in our understanding of how vascular factors contribute to Alzheimer's disease and related dementia has been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an interest in hyperglycemia-driven neuroinflammation, which may compromise the integrity of BBB with increased permeability that leads to memory loss and impaired cognition [18]. This, along with the increasing interest in the vascular contributions to cognitive impairment and dementia, wherein scientific experts convened to discuss the research gaps in our understanding of how vascular factors contribute to Alzheimer's disease and related dementia has been discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In KKA y mice, a model of type II diabetes, Min et al demonstrated that blocking angiotensin II type 1 receptors to activate peroxisome proliferator-activated receptor (PPAR)-γ protected against cognitive decline by preserving the integrity of the BBB [11]. More recently, Rom et al published a paper examining BBB disruption using the fluorescent tracer, sodiumfluorescein (NaF) in the leptin receptor deficient db/ db mouse model [12]. These publications assessed BBB integrity using either non-quantitative techniques such as Evans Blue or IgG extravasation or non-reliable quantitative methods such as sodium fluorescein [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the clearance of βA in the brain is associated with an IDE. Therefore, development of IDE activators could be one of the possible drugable target in AD (Matioli & Nitrini, 2015;Pivovarova, Höhn, Grune, Pfeiffer, & Rudovich, 2016;Rom et al, 2019).…”
Section: Insulin-degrading Enzymementioning
confidence: 99%